Enhanced thioredoxin, glutathione and Nrf2 antioxidant systems by safflower extract and aceglutamide attenuate cerebral ischaemia/reperfusion injury. Issue 9 (7th April 2020) - Zhang, Jingjing; Zhou, Rui; Xiang, Changpei; Fan, Fangfang; Gao, Jinhuan; Zhang, Yi; Tang, Shihuan; Xu, Haiyu; Yang, Hongjun
Abstract: A large number of reactive oxygen species (ROS) aggravate cerebral damage after ischaemia/reperfusion (I/R). Glutathione (GSH), thioredoxin (Trx) and nuclear factor (erythroid‐derived 2)‐like 2 (Nrf2) represent three major antioxidant systems and play vital roles in affecting each other in eliminating ROS. Identification of drugs targeting triple antioxidant systems simultaneously is vital for inhibiting oxidative damage after cerebral I/R. This study investigated the protective effect of safflower extract and aceglutamide (SAAG) against cerebral I/R injury through modulating multiple antioxidant systems of GSH, Trx and Nrf2 and identified each role of its component acegluatminde (AG) and safflower extract (SA) on these systems. Safflower extract and aceglutamide and its two components decreased neurological deficit scores, infarction rate, apoptosis and oxidative damage after cerebral I/R while enhanced cell viability, decreased reactive oxygen species and nitric oxide level in H2 O2 ‐induced PC12 cell model. Importantly, compared to its two components, SAAG demonstrated more effective enhancement of GSH, Nrf2 and Trx systems and a better protection against cerebral I/R injury. The enhanced antioxidant systems prevented ASK1 activation and suppressed subsequent p38 and JNK cascade‐mediated apoptosis. Moreover, inhibition of Trx and Nrf2 systems by auranofin and ML385 abolished SAAG‐mediated protection, respectively. Thus, enhanced triple systems by SAAG played a better protective role than those by SA or AG via inhibition of ASK1 cascades. This research provided evidence for the necessity of combination drugs from the perspective of multiple antioxidant systems. Furthermore, it also offers references for the study of combination drugs and inspires novel treatments for ischaemic stroke.